The hunger habit : why we eat when we're not hungry and how to stop - Brewer, Judson (Avery, an imprint of Penguin Random House, 2024)
"A program proven to heal our relationship with food and our bodies from New York Times bestselling author of Unwinding Anxiety. Anyone who struggles with overeating knows what it's like to feel out of control-and to feel the guilt attached to it. While ordinary anxiety feels like something that happens to us, the siren song of food cravings feels like something we should be able to control. The result is a toxic cocktail of shame and self-loathing that makes it impossible to change our behavior. The Hunger Habit is based on Judson Brewer's deeply researched plan proven to help us understand what is going on in our brains so that we can heal the shame and overcome overeating. The step-by-step program focuses on the power of awareness-there is no willpower, calorie-counting, or restricted eating. Setbacks are a good thing! The key is to learn how to work with our brains rather than to fight cravings, and to adopt an attitude of self-kindness rather than self-judgment. Grounded in cutting-edge neuroscience, The Hunger Habit is both accessible and compassionate. It will finally help you break out of food jail and reclaim your life"--